On Welfare Effects of Increasing Retirement Age - Krzysztof Makarski; Joanna Tyrowicz (Institute of Labor Economics (IZA), 2018)
We develop an OLG model with realistic assumptions about longevity to analyze the welfare effects of raising the retirement age. We look at a scenario where an economy has a pay-as-you-go defined benefit scheme and compare it to a scenario with defined contribution schemes (funded or notional). We show that, initially, in both types of pension system schemes the majority of welfare effects comes from adjustments in taxes and/or prices. After the transition period, welfare effects are predominantly generated by the preference for smoothing inherent in many widely used models. We also show that although incentives differ between defined benefit and defined contribution systems, the welfare effects are of comparable magnitude under both schemes. We provide an explanation for this counter-intuitive result.
Keywords: C68; E21; J11; H55; 330; longevity; PAYG; retirement age; pension system reform; welfare